Key Risk Determinants of Listed Deposit-Taking Institutions in Malaysia (Malaysian Management Journal, 2004)
Risk management is a critical function in banking operations in the wake of several banking crises. However, we find few studies on risk management and a lack of empirical investigation on factors affecting the risk of Malaysian banks. These gaps have motivated us to identify the main factors associated with the risk of locally listed deposit-taking institutions. The findings show that three factors were significantly associated with unsystematic risk, while the systematic risk and the total risk of these deposit-taking institutions were significantly affected by four main factors. These four factors namely non-performing loans, cost of funds, loan to deposit ratio and inter-bank offered rate however, were found to have a more profound effect on the total risk than on the systematic risk or the unsystematic risk of Malaysian deposit-taking institutions.